Myśli o edukacji z perspektywy ideologii (edukacyjnych?) jako wartościowych społeczno-politycznych analiz i refleksji = Considerations on education from the perspective of (educational?) ideologies as valuable socio-pedagigical analyses and reflections - Kowalski, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Strategies of ideologization of education used by politicians take the form of active and relatively open (overt) ideologization, among others, of analytical and rhetorical practices in education. They are elements of relatively clear strategies of political and public rhetoric. Usually, they do not take refined forms. Which ideological elements are "blended" with particular educational elements, who is responsible for the blending, and what the person wants to politically achieve with this is quite transparent.
Keywords: edukacja; szkolnictwo wyższe; polityka oświatowa; education; higher education; educational policy